Effects of metformin and simvastatin treatment on ultrastructural features of liver macrophages in HFD mice. (2nd January 2023) - Ciric, Darko; Kravic-Stevovic, Tamara; Bumbasirevic, Vladimir; Petricevic, Sasa; Jovanovic, Sofija; Trajkovic, Vladimir; Martinovic, Tamara
ABSTRACT: Type 2 diabetes is a major health burden to the society. Macrophages and liver inflammation emerged as important factors in its development. We investigated ultrastructural changes in the liver, with a special emphasis on macrophages in high fat diet (HFD) fed C57BL/6 J mice treated with metformin or simvastatin, two drugs that are used frequently in diabetes. Both metformin and simvastatin reduced the liver damage in HFD fed animals, manifested as the prevention of nonalcoholic steatohepatitis development and reduced activation and number of macrophages in the liver, as well as the percentage of these cells with lipid droplets in the cytoplasm compared to untreated HFD animals. In contrast with untreated HFD-fed animals, lipid droplets were not observed in lysosomes of macrophages in HFD animals treated with metformin and simvastatin. These findings provide new insight into the effects of metformin and simvastatin on the liver in this experimental model of type 2 diabetes and provide further rationale for implementation of statins in the therapeutic regimens in this disease.